Cognitive Function and Serum Hormone Levels Are Associated with Gray Matter Volume Decline in Female Patients with Prolactinomas - Yao, Shun; Song, Jian; Gao, Junfeng; Lin, Pan; Yang, Ming; Zahid, Kashif Rafiq; Yan, Yan; Cao, Chenglong; Ma, Pan; Zhang, Hui; Li, Zhouyue; Huang, Cheng; et al. (Frontiers in Neurology, 2018)
Background and objective: Cognitive impairments have been reported in patients with hyperprolactinemia; however, there is a lack of knowledge of brain structure alterations relevant to hyperprolactinemia in prolactinomas. Thus, we aimed to identify changes in brain structure in prolactinomas, and to determine whether these changes are related to cognitive performance and clinical characteristics. Methods: Participants were 32 female patients with prolactinomas and 26 healthy controls matched for age, sex, education, and handedness. All participants underwent magnetic resonance imaging (MRI) brain scans, neuropsychological assessments, and clinical evaluations. Voxel-based morphometry analysis was used to identify changes in gray matter volume (GMV). Partial correlation analysis and multiple linear regression were performed to determine the relationship between GMV, cognition, and clinical characteristics. Results: Compared to healthy controls, patients with prolactinomas demonstrated a decrease in GMV in the left hippocampus, left orbitofrontal cortex (OFC), right middle frontal cortex (MFC), and right inferior frontal cortex (IFC). In addition, patients performed worse than controls on tests for verbal memory and executive function, and this was significantly related to the GMV of the left hippocampus and right MFC, respectively. Moreover, in the patients, we found a negative relationship between serum prolactin levels and the GMV of the left hippocampus and right IFC, whereas a positive relationship was found between the GMV of the left hippocampus and serum levels of estradiol and luteinizing hormone. Conclusion: In patients with prolactinomas, specific brain structure abnormalities have been identified and are associated with cognitive impairments and dysfunctional hormones. This study enhances our understanding of brain structure changes that may occur with prolactinomas and provides novel and fundamental evidence for previous behavioral findings relevant to hyperprolactinemia.